Supreme injustice slavery in the nation's highest court - Finkelman, Paul, 1949- (Harvard University Press, 2018)
"In ruling after ruling, the three most important pre-Civil War justices--Marshall, Taney, and Story--upheld slavery. Paul Finkelman establishes an authoritative account of each justice's proslavery position, the reasoning behind his opposition to black freedom, and the personal incentives that embedded racism ever deeper in American civic life"--